Pharmakon landscape: An emerging territorial model for deep-time, geo-bio-chemical governance - Brina, Luciano (Interstices: Journal of Architecture and Related Arts, 2022)
This paper is a further development of the contents and topics from a homonymous microfilm produced in mid-2020, in the context of The Terraforming postgraduate programme at Strelka Institute for Media, Architecture and Design, Moscow. In that sense, it aims to bring the speculations depicted in the film closer to their realisation, by means of territorial initiatives and key facts. Pharmakon landscape intends to be a model of intense territorial intervention for climate change mitigation and geo-bio-chemical governance. Dedicated to ecological services fulfillment and its management, it converges in waste manipulation, infrastructural repurposing, rewilding, and direct human intervention limiting. It is a geodesign initiative that challenges the clear boundaries between what remedy, poison, and scapegoat mean: here, poisoning equals accelerated remediation, so that the ambivalent coexistence of this conceptual triad becomes co-dependency.